Outcome of Hypertonic Saline Versus Normal Saline in Children with Acute Bronchiolitis - Sidra Shahid, Asif Javeed, Saba Wamiq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare outcome of hypertonic saline (HS) versus normal saline (NS) among children aged 2 to 24 months with acute bronchiolitis. Study design: An open label randomized controlled trial. Place and Duration of the Study: Department of Pediatric Medicine, Ibn-e-Siena Hospital, Multan from 1st September 2021 to 31st March 2022. Methodology: A total of 220 children (110 in each group) of both genders aged 2 to 24 months reporting to emergency department with acute bronchiolitis with a disease spanning less than 5 days were included. In HS group, children were nebulized with 4 ml of 3% HS while in NS groups, all children were nebulized with 4ml 0.9% saline solution. In both groups, children were given respective treatment with interval gap of 4 hours. Clinical severity score and need for hospitalization after 24 hours was noted. Results: In a total of 220 children, 126 (57.3%) were males and 94 (42.7%) females. Overall, mean age was 7.9±5.3 months while 170 (77.3%) children were aged between 2 to 12 months. Residential status of 132 (60.0%) children was rural. Monthly family income of 165 (75.0%) children was below 25,000 Pakistani Rupees (PKR). Maternal educational status of 91 (41.4%) children was illiterate. Mean baseline clinical severity score was calculated to 7.28 ± 1.47. HS group, post-treatment mean clinical severity score was 4.29±2.83 in comparison to 5.99±2.64 in NS groups. There were 28 (25.5%) children in HS group who required hospitalization in comparison to 56 (50.9%) in NS group (p=0.0001) Conclusion: In comparison to nebulization with normal saline, nebulization with hypertonic saline solution was found to be significantly more effective in reducing clinical severity score and need for hospitalization among children aged up to 2 years with acute bronchiolitis. Keywords: Hypertonic saline, normal saline, acute bronchiolitis, clinical severity score.